Eculizumab in Pediatric Kidney Disorders: A Review: Eculizumab in Kidney Disorders - Jamee, Mahnaz; Farsi, Yeganeh; Akhondi, Amir Hossein; Kamali, Farnaz; Hajialigol, Amir Hossein; Mirzaee, Mahbubeh; Mohkam, Masoumeh (Journal of Pediatric Nephrology, 2022)
Eculizumab is a humanized monoclonal antibody targeting the C5 (complement 5) member of complement proteins and inhibiting its cleavage to C5a and C5b. Eculizumab has been proven to be effective in a wide array of nephrologic, neurologic, and hematologic pediatric disorders. Kidney disorders, particularly those with immune-mediated pathomechanism, are the most common indications of eculizumab, including atypical hemolytic uremic syndrome (aHUS), hemolytic uremic syndrome (HUS), membranoproliferative glomerulonephritis (MPGN), immunoglobulin A (IgA) nephropathy, hematopoietic stem cell transplant-associated thrombotic microangiopathy, and less commonly post-infectious glomerulonephritis and diffuse proliferative lupus nephritis. In this review, we aimed to summarize the current evidence on approved and off-label applications of eculizumab and their specific considerations in pediatric kidney disorders.